Therapeutic Effects of (5R)-5-Hydroxytriptolide on Fibroblast-Like Synoviocytes in Rheumatoid Arthritis via lncRNA WAKMAR2/miR-4478/E2F1/p53 Axis - Zhou, Xinpeng; Xie, Duoli; Huang, Jie; Lu, Aiping; Wang, Rongsheng; Jin, Yehua; Zhang, Runrun; Chang, Cen; Xu, Lingxia; Xu, Linshuai; Fan, Junyu; Liang, Chao; et al. (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is an autoimmune disease. Fibroblast-like synoviocytes (FLS) serve a major role in synovial hyperplasia and inflammation in RA. (5R)-5-Hydroxytriptolide (LLDT-8), a novel triptolide derivative, shows promising therapeutic effects for RA and is now in phase II clinical trials in China. However, the underlying mechanism of LLDT-8 is still not fully understood. Here, we found that LLDT-8 inhibited proliferation and invasion of RA FLS as well as production of cytokines. Microarray data demonstrated that LLDT-8 upregulated expression of long non-coding RNA (lncRNA) WAKMAR2, which was negatively associated with proliferation and invasion of RA FLS as well as production of pro-inflammatory cytokines. Knockdown of WAKMAR2 abolished the inhibitory effects of LLDT-8 on RA FLS. Mechanistically, WAKMAR2 sponged miR-4478, which targeted E2F1 and downstream p53 signaling. Rescue experiments indicated that the inhibitory effects of LLDT-8 on RA FLS were dependent on WAKMAR2/miR-4478/E2F1/p53 axis.